Step
*
3
of Lemma
bag-null-filter
1. T : Type
2. p : T ⟶ 𝔹
3. u : T
4. ¬↑p[u]
5. v : T List
6. ∀x:T. (x ↓∈ v 
⇒ (¬↑p[x])) supposing ↑bag-null([x∈v|p[x]])
7. ↑bag-null([x∈v|p[x]]) supposing ∀x:T. (x ↓∈ v 
⇒ (¬↑p[x]))
8. ∀x:T. (x ↓∈ u.v 
⇒ (¬↑p[x]))
⊢ [x∈v|p[x]] = {} ∈ bag({x:T| ↑p[x]} )
BY
{ (All (RW assert_pushdownC) THENA Auto) }
1
1. T : Type
2. p : T ⟶ 𝔹
3. u : T
4. ¬↑p[u]
5. v : T List
6. ∀x:T. (x ↓∈ v 
⇒ (¬↑p[x])) supposing [x∈v|p[x]] = {} ∈ bag({x:T| ↑p[x]} )
7. [x∈v|p[x]] = {} ∈ bag({x:T| ↑p[x]} ) supposing ∀x:T. (x ↓∈ v 
⇒ (¬↑p[x]))
8. ∀x:T. (x ↓∈ u.v 
⇒ (¬↑p[x]))
⊢ [x∈v|p[x]] = {} ∈ bag({x:T| ↑p[x]} )
Latex:
Latex:
1.  T  :  Type
2.  p  :  T  {}\mrightarrow{}  \mBbbB{}
3.  u  :  T
4.  \mneg{}\muparrow{}p[u]
5.  v  :  T  List
6.  \mforall{}x:T.  (x  \mdownarrow{}\mmember{}  v  {}\mRightarrow{}  (\mneg{}\muparrow{}p[x]))  supposing  \muparrow{}bag-null([x\mmember{}v|p[x]])
7.  \muparrow{}bag-null([x\mmember{}v|p[x]])  supposing  \mforall{}x:T.  (x  \mdownarrow{}\mmember{}  v  {}\mRightarrow{}  (\mneg{}\muparrow{}p[x]))
8.  \mforall{}x:T.  (x  \mdownarrow{}\mmember{}  u.v  {}\mRightarrow{}  (\mneg{}\muparrow{}p[x]))
\mvdash{}  [x\mmember{}v|p[x]]  =  \{\}
By
Latex:
(All  (RW  assert\_pushdownC)  THENA  Auto)
Home
Index